The Effect of Vitamin D3 and Co-enzyme Q10 Supplementation on Metabolic Biomarkers in Women with Clomiphene Citrate Resistant Polycystic Ovary Syndrome - Ansam Abdulameer Yahya; Manal Khalid Abdulridha; Bushra Jassim Al-Rubuyae (College of Pharmacy / Mustansiriyah University, 2018)
Polycystic ovary syndrome (PCOS) one of the most common endocrine disorders in women of reproductive age, the pathogenesis of PCOS imitated to be as a vicious cycle involving both hyperandrogenaemia and insulin resistance/hyperinsulinemia. Vitamin D deficiency (VDD) is common among women with PCOS (approximately 67%-85% women with PCOS have VDD). Vitamin D3 and CoQ10 could affect glucose metabolism and insulin sensitivity and improve metabolic abnormalities in PCOS. The study was designed to evaluate the effect of combining oral vitamin D3 tablet or CoQ10 capsule with clomiphene citrate on metabolic biomarkers in women with clomiphene citrate resistance PCOS patients. A prospective interventional randomized-controlled, open-label study include 41 PCOS patients aged range (18-34)years who are clomiphene citrate resistant divided into two groups, group 1 (n=24)  whose endogenous vitamin D status less than 20ng/ml receive clomiphene citrate 100mg daily(for 5 days monthly induction) plus vitamin  D 10000IU daily (2 months) and group 2 (n=17) whose endogenous vitamin D status equal or more than 20ng/ml receive clomiphene citrate 100mg daily(for 5 days monthly induction) plus CoQ10 200mg daily (2 months). Fasting blood samples were taken at baseline and 2 months after intervention to measure metabolic biomarkers [fasting serum insulin (FSI), fasting blood glucose (FBG), homeostatic model assessment of insulin resistance (HOMA-IR), quantitative insulin sensitivity check index (QUICKI)]. After 2 months both interventions result in non-significant change in FSI and FBG while HOMA-IR and QUICKI decreased by both interventions, but the decrease is significant only with CoQ10 supplementations. In conclusion, Vitamin D and CoQ10 supplementation result in improvement in HOMA-IR and QUICKI but the improvement was more obvious in CoQ10 group.